A microRNA signature associated with pathological complete response to novel neoadjuvant therapy regimen in triple-negative breast cancer - Raúl García-Vazquez; Erika Ruiz-García; Abelardo Meneses García; Horacio Astudillo-de la Vega; Fernando Lara-Medina; Alberto Alvarado-Miranda; Héctor Maldonado-Martínez; Juan A González-Barrios; Alma D Campos-Parra; Sergio Rodríguez Cuevas; Laurence A Marchat; César López-Camarillo (Tumor Biology)
Neoadjuvant chemotherapy aims to improve the outcome of breast cancer patients, but only few would benefit from this treatment. Pathological complete response has been proposed as a surrogate marker for the prediction of long-term clinical benefits; however, 50%–85% patients have an unfavorable pathological complete response to chemotherapy. MicroRNAs are known biomarkers of breast cancer progression; nevertheless, their potential to identify patients with pathological complete response remains poorly understood. Here, we investigated whether a microRNA profile could be associated with pathological complete response in triple-negative breast cancer patients receiving 5-fluorouracil, adriamycin, cyclophosphamide–cisplatin/paclitaxel as a novel neoadjuvant chemotherapy. In the discovery cohort, the expression of 754 microRNAs was examined in tumors from 10 triple-negative breast cancer patients who achieved pathological complete response and 8 without pathological complete response using TaqMan Low-Density Arrays. Unsupervised hierarchical cluster analysis identified 11 microRNAs with significant differences between responder and no-responder patients (fold change ≥ 1.5; p < 0.05). The differential expression of miR-30a, miR-9-3p, miR-770, and miR-143-5p was validated in an independent group of 17 patients with or without pathological complete response. Moreover, Kaplan–Meier analysis showed that expression of these four microRNAs was associated with an increased disease-free survival. Gene ontology classification of predicted microRNA targets indicated that numerous genes are involved in pathways related to chemoresistance, such as vascular endothelial growth factor, focal adhesion kinase, WNT, ERbB, phosphoinositide 3-kinase, and AKT signaling. In summary, we identified a novel microRNA expression signature associated with pathological complete response in breast cancer. We propose that the four validated microRNAs could be used as molecular biomarkers of clinical response in triple-negative breast cancer patients with pathological complete response to neoadjuvant therapy.